Institutional delivery service utilization and associated factors among mothers who gave birth in the last 12 months in Sekela District, North West of Ethiopia: A community - based cross sectional study - Teferra Alemayehu; Alemu Fekadu; Woldeyohannes Solomon (BMC, 2012)
Abstract Background Reduction of maternal mortality is a global priority particularly in developing countries including Ethiopia where maternal mortality ratio is one of the highest in the world. The key to reducing maternal mortality ratio and improving maternal health is increasing attendance by skilled health personnel throughout pregnancy and delivery. However, delivery service is significantly lower in Amhara Regional State, Ethiopia. Therefore, this study aimed to assess factors affecting institutional delivery service utilization among mothers who gave birth in the last 12 months in Sekela District, Amhara Region, Ethiopia. Methods Community-based cross-sectional study was conducted among mothers with birth in the last 12 months during August, 2010. Multistage sampling technique was used to select 371 participants. A pre tested and structured questionnaire was used to collect data. Bivariate and multivariate data analysis was performed using SPSS version 16.0 software. Results The study indicated that 12.1% of the mothers delivered in health facilities. Of 87.9% mothers who gave birth at home, 80.0% of them were assisted by family members and relatives. The common reasons for home delivery were closer attention from family members and relatives (60.9%), home delivery is usual practice (57.7%), unexpected labour (33.4%), not being sick or no problem at the time of delivery (21.6%) and family influence (14.4%). Being urban resident (AOR [95% CI] = 4.6 [1.91, 10.9]), ANC visit during last pregnancy (AOR [95% CI] = 4.26 [1.1, 16.4]), maternal education level (AOR [95%CI] =11.98 [3.36, 41.4]) and knowledge of mothers on pregnancy and delivery services (AOR [95% CI] = 2.97[1.1, 8.6]) had significant associations with institutional delivery service utilization. Conclusions Very low institutional delivery service utilization was observed in the study area. Majority of the births at home were assisted by family members and relatives. ANC visit and lack of knowledge on pregnancy and delivery services were found to be associated with delivery service utilization. Strategies with focus on increasing ANC uptake and building knowledge of the mothers and their partners would help to increase utilization of the service. Training and assigning skilled attendants at Health Posta level to provide skilled home delivery would improve utilization of the service.